ACCRUALIZATION IN THE PUBLIC SECTOR: THE CASE OF SITUBONDO DISTRICT - Sari, Lita Permata; Djamhuri, Ali; Kamayanti, Ari (Accounting Department,, 2014)
The move from cash to accruals accounting by many governmentsis viewed as an aspect of an ongoing New Public Management agenda designed to achievea more business-like and Performance – focused public sector.This paper examines the process of change in the Situbondo district early adoption of accrual based fiancial reporting. The study’s main objective is to present a history that identifis the agents of change promoting and facilitating an early adoption of public sector accrual accounting. The main primary data source for this research was interviews with key actors. The result shows that changes from cash basis to the accrual into accrual basis as the Government Regulation No. 71 of 2010.Keywords: accrual accounting, organization change, new institutional theory